AB0364 EFFICACY OF BARICITINIB (BARI) IN PATIENTS WITH RHEUMATOID ARTHRITIS (RA) WHOSE RESPONSE WAS INADEQUATE TO TOFACITINIB (TOFA). (13th June 2020) - Yamane, T.; Hashiramoto, A.
Abstract : Background: Currently, four types of JAK inhibitors are approved for the treatment of RA in Japan, however, they often show differences in clinical efficacies presumably due to their JAK selectivity. Objectives: To investigate the efficacy of Bari for patients with Tofa-inadequate response (IR), clinical profiles of seven Tofa IR patients were evaluated. Methods: We performed a single-center retrospective study on seven Tofa IR patients (female:7) who were switched to Bari. Items evaluated were as follows; patient's baseline characteristics, continuation rate of Bari, swollen joint count, tender joint count, C-reactive protein (CRP), matrix proteinase 3 (MMP3), physician's and patient's visual analog scale (VAS), disease activity assessed by Disease Assessment Score of 28 joints - C-reactive protein (DAS 28-CRP), simplified disease activity index (SDAI) and clinical disease activity index (CDAI) at 2, 4, 8, 12 weeks, and the dosage of prednisone (PSL). Results: Patient's mean age was 56.4 and mean disease duration was 9.2 years. Tofa had administered for 3.4 months (range 1-10) before switching to Bari. All patients were positive for both anti-citrullinated protein antibodies and rheumatoid factor. The number of prior biologics use was 2.3 (range1-4). 3 patients had concomitant MTX use (mean dosage 5.3 mg/week) and 4 had prednisone (mean dosage 3.3 mg/day). Mean swollen joint counts and tender joint counts were 5.0 (range 1-15) and 5.3 (range 1-15), respectively. Physician's and Patient's VAS 0-100 were 71 mm (range 50-90) and 73 mm (range 50-80), mean CRP levels were 1.6 mg/dl (range 0.01-4.3) and MMP3 levels were 357.3 mg/dl (range 27-933). Mean SDAI, CDAI and DAS-28-CRP were 26.3 (range17-50), 24.7 (range17-47) and 4.5, respectively. When enrolled, 4 of 7 patients corresponded to moderate disease activity (MDA) and 3 were in high disease activity (HDA) by all composite measures. After switched to Bari, the patient's VAS significantly decreased at week 2 (P <0.01). CDAI, SDAI and DAS28-CRP also showed a significant improvement at week 4, (P <0.05). At week 4, 2 patients discontinued Bari due to the lack of efficacy or acute exacerbation of interstitial pneumonia. Thus, continuation rate of Bari at week 12 was 71.4%. Among 5 patients who continues Bari, all patients achieved low disease activity (LDA) by SDAI and CDAI at week 12. By DAS 28-CRP, 2 patients achieved MDA, 2 achieved LDA and 1 achieved remission (mean 2.6), respectively, at week 12, 3 of 4 patients taking PSL were able to withdraw that before week 12 (Figure). Conclusion: Result showed the efficacy of Bari for patients with Tofa IR, representing inadequate improvements of patient's VAS with Tofa. The efficacy of Bari can be expected from the early stage and continued up to 12 weeks after switching. This difference in therapeutic effect may be due to each mechanism of action, Bari inhibits JAK1/2, whereas Tofa mainly inhibits JAK1 /3 (1). JAK2 is important for signal by GM-CSF, which has shown potential as an important therapeutic target in RA (2).Inhibition of JAK2 and GM-CSF may be the reason for Bari efficacy in Tofa IR patients. References: [1]O'Shea JJ et al. Back to the future: oral targeted therapy for RA and other autoimmune diseases. Nat Rev Rheumatol 2013 Mar;9(3):173-82. [2]Wicks IP et al. Targeting GM-CSF in inflammatory diseases. Nat Rev Rheumatol. 2016 Jan;12(1):37-48. Disclosure of Interests: None declared